1995
DOI: 10.1113/jphysiol.1995.sp020911
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of energy output during ramp and staircase shortening in frog muscle fibres.

Abstract: 1. We compared the rates of work and heat production during ramp shortening with those during staircase shortening (sequence of step releases of the same amplitude, separated by regular time intervals). Ramp or staircase shortening was applied to isolated muscle fibres (sarcomere length, 2-2 ,sm; temperature, 1 00) at the plateau of an isometric tetanus. The total amount of shortening was no greater than 6 % of the fibre length. 2. During ramp shortening the power output showed a maximum at about 0-8 fibre len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 27 publications
5
26
1
1
Order By: Relevance
“…4). This may be consistent with the result that a roughly proportional relationship exists between the rate of ATP utilization and the fibre shortening velocity (Reggiani et al, 1997;He et al, 2000;Potma and Stienen, 1996), but not with the biphasic relationship between the rate of energy liberation (heat + work) and the shortening velocity in whole muscle (Hill, 1964;Linari and Woledge, 1995). The approximately linear dependence of the amount of ATP utilized for work production on the distance of shortening (Fig.…”
Section: Relationship With Previous Studiessupporting
confidence: 77%
“…4). This may be consistent with the result that a roughly proportional relationship exists between the rate of ATP utilization and the fibre shortening velocity (Reggiani et al, 1997;He et al, 2000;Potma and Stienen, 1996), but not with the biphasic relationship between the rate of energy liberation (heat + work) and the shortening velocity in whole muscle (Hill, 1964;Linari and Woledge, 1995). The approximately linear dependence of the amount of ATP utilized for work production on the distance of shortening (Fig.…”
Section: Relationship With Previous Studiessupporting
confidence: 77%
“…These increases were larger than those (2 times in EDL and even less in soleus) observed by Heglund & Cavagna (1987) and opposite to those (5 times in the soleus and 1·6 times in the EDL) reported by Barclay et al (1993). Similar increases have been observed in frog single fibres at low temperature: for example, Linari & Woledge (1995) found that, when fibres shortened at about 60% Vmax, the rate of total energy output was 6 times higher than in isometric conditions. The comparison between different studies is, however, made difficult by possible influences of temperature and sarcomere length (for a review see Rall, 1982;and Woledge, Curtin & Homsher, 1985) and by the presence of non-myofibrillar sources of energy consumption in whole muscles as well as in intact single fibres.…”
Section: Discussionmentioning
confidence: 40%
“…described in detail in frog muscles and single fibres (Fenn, 1924;Hill, 1938;Woledge, 1968;Irving & Woledge, 1981;Linari & Woledge, 1995). Contrasting results have been obtained from the calculation of efficiency as the ratio of mechanical power output to the rate of energy consumption.…”
mentioning
confidence: 92%
“…Muscle power vT(v) per myofilament (Fig. 6d) 34 ; it is not clear that a maximum rate for v < v o has been observed in frog sartorius muscle. As a function of v, the predicted efficiency of energy conversion has the expected shape, rising to a maximum of 0.6 at v = 300 nm/s.…”
Section: Steady Shorteningmentioning
confidence: 99%
“…These slower phases can be associated with cycling heads. 7,34,49 Predictions for the phase-2 response of the model are presented in Fig. 8.…”
Section: Length Stepsmentioning
confidence: 99%